ANALISIS PENERAPAN PRA-ANALITIK DAN ANALITIK KUALITAS SEDIAAN BTA METODE ZIEHL-NEELSEN DI PUSKESMAS KECAMATAN CIRACAS JAKARTA TIMUR - Cut Nur Masita; Dian Rachma Wijayanti; Sabarina Elfrida Manik (Jurnal SainHealth, 2024)
The microscopic examination of BTA with sputum samples aims to detect the onset and monitoring of treatment in tuberculosis. The purpose of this study is to find out the Analysis of the application of six preanalytic and analytical indicators to the quality of acid-resistant basil preparation using the Ziehl-Neelsen method at the East Jakarta Ciracas Subdistrict Health Center, which was conducted in April-June 2023. The type and design of the study are analytical cross-sectional, data analyzed using the Chi-Square test. BTA prepared quality results by performing six indicators, proportionally greater good prepared quality than poor prepared quality with 90% specimen quality percentage, 95% preparation quality, 85% preparation cleanliness, 90% preparation size, 92.5%, and 92.5% preparation accuracy. An analysis of the application of six pre-analytic and analytic indicators to the quality of the acid-resistant basil supply using the Ziehl-Neelsen method at the East Jakarta Ciracas Subdistrict Health Center which includes specimen quality, preparation cleanliness, preparation thickness, and preparation accuracy showed a meaningful relationship. The coloring of the preparedness and the size of the preparedness indicates no meaningful relationship.